The Impact of Accounting Information Systems, Internal Audit, and Human Resource Quality on Employee Performance at PT. Bumi Berdikari Sentosa - Wina Raida Anggraini, Cut; Puspitasari, Dian Puji; Marlina, Evi (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2024)
This study aims to examine the influence of accounting information systems, internal audit, and the quality of human resources on employee performance at PT. Bumi Berdikari Sentosa. The data collection method employed in this research is a questionnaire. The population consists of all 55 employees of PT. Bumi Berdikari Sentosa, with a sample of 45 employees selected through purposive sampling. The data analysis techniques used include descriptive analysis, data quality testing, classical assumption testing, multiple linear regression analysis, hypothesis testing, and the coefficient of determination test.The findings reveal that the accounting information system has a significant positive effect on employee performance. In contrast, internal audit does not show a significant effect on employee performance. Meanwhile, the quality of human resources significantly influences employee performance.